From knowledge to added value: A comparative, panel-data analysis of the innovation value chain in Irish and Swiss manufacturing firms - Stephen Roper; Spyros Arvanitis (ETH Zurich, KOF Swiss Economic Institute, 2009)
The innovation value chain (IVC) divides the innovation process into three separate links or activities: knowledge gathering, knowledge transformation and knowledge exploitation. Here, we report a comparative panel data analysis of the IVC in Ireland and Switzerland. Both economies are small, very open and depend significantly on innovation to maintain competitive advantage. In recent years, however, R&D and innovation growth in Ireland has been markedly stronger than that in Switzerland. We investigate these differences through the lens of the IVC. We identify significant similarities between the determinants of firms' knowledge gathering behaviours in each country although firms are responding differently to financial and legal constraints. Strong complementarities emerge between external knowledge sources and between firms' internal and external knowledge. In terms of knowledge transformation - the development of new products or processes - we again find strong similarities between the two countries in terms of the determinants of the probability of innovation. The determinants of innovation intensity vary more, however, with external ownership significantly more important in Ireland. Finally, we consider the link between innovation and productivity which involves significant endogeneity issues. Two-stage estimation procedures do not suggest any significant links between innovation and productivity as we might expect from the macro-economic evidence.
Keywords: O3; O5; P5; 330; Innovation; value chain; Switzerland; Ireland; Innovation; Industrielle Forschung; Verarbeitendes Gewerbe; Irland; Schweiz